IFRS Adoption Models in Islamic Banks of South Africa and Indonesia: A Systematic Literature Review - Sujana, Deni Amin; Mukhlisin, Murniati (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2025)
This study undertakes a comparative analysis of the implementation models of International Financial Reporting Standards (IFRS) in South Africa and Indonesia, focusing specifically on Islamic banking institutions. Whereas South Africa pursued full adoption of IFRS to align with international reporting benchmarks, Indonesia opted for a convergence approach, integrating IFRS principles within its existing local financial reporting framework. Employing a Systematic Literature Review (SLR) methodology, this research synthesizes findings from academic literature, annual reports of Islamic banks, and relevant institutional progress reports on IFRS implementation. The findings indicate that full IFRS adoption in South Africa has enhanced financial reporting quality and transparency; however, it has not entirely mitigated earnings management practices, such as income smoothing. Conversely, Indonesia’s convergence model facilitates the preservation of distinct Shariah-compliant accounting standards but encounters persistent challenges in achieving full harmonization with global frameworks, including IFRS and AAOIFI. The study highlights the critical importance of tailoring IFRS implementation strategies to national regulatory landscapes while simultaneously respecting the unique principles governing Islamic finance. These insights contribute to the broader academic discourse on navigating the complexities of balancing global financial comparability with religious and cultural compliance within the context of Islamic banking. ======================================================================================================== ABSTRAK - Model Adopsi IFRS pada Bank Syariah di Afrika Selatan dan Indonesia: Systematic Literature Review. Penelitian ini bertujuan untuk menganalisis perbandingan model implementasi International Financial Reporting Standards (IFRS) antara Afrika Selatan dengan Indonesia, yang berfokus pada perbankan syariah. Sementara Afrika Selatan menerapkan adopsi penuh IFRS guna menyelaraskan pelaporan keuangannya dengan tolok ukur internasional, Indonesia memilih pendekatan konvergensi, mengintegrasikan prinsip-prinsip IFRS ke dalam kerangka standar pelaporan keuangan lokal yang telah ada. Menggunakan metodologi Systematic Literature Review (SLR), penelitian ini mensintesis temuan dari literatur akademik, laporan tahunan bank syariah, serta laporan perkembangan institusional yang relevan terkait implementasi IFRS. Hasil kajian menunjukkan bahwa adopsi penuh IFRS di Afrika Selatan telah meningkatkan kualitas dan transparansi pelaporan keuangan; namun demikian, praktik manajemen laba, seperti perataan laba (income smoothing), belum sepenuhnya termitigasi. Sebaliknya, model konvergensi Indonesia memfasilitasi pelestarian standar akuntansi berbasis Syariah yang khas, tetapi menghadapi tantangan berkelanjutan dalam mencapai harmonisasi penuh dengan kerangka kerja global, termasuk IFRS dan AAOIFI. Studi ini menekankan pentingnya penyesuaian strategi implementasi IFRS dengan lanskap regulasi nasional, sembari tetap menghormati prinsip-prinsip unik yang mengatur keuangan Syariah. Temuan ini berkontribusi pada diskusi akademik yang lebih luas mengenai pengelolaan kompleksitas dalam menyeimbangkan keterbandingan keuangan global dengan kepatuhan religius dan budaya dalam konteks perbankan syariah.